Answers

2014-06-07T15:28:07+08:00
2x(3x-1) = 6 x^{2} -2x
(4a ^{5} )(1-2 a^{2} ) = 4 a^{5} -8a ^{7}
 x^{3} (4 x^{2} +3 x^{6}) = 4  x^{5} +3 x^{9}
3 m^{2} (2+3 m^{2} -4 x^{4}) = 6 m^{2}  + 9 m^{4}  - 12 m^{6}
-4ab( b^{4} -5 a^{2} ) =-4ab^{2} + 20 a^{2} b
(5pq) (1+ 5 p^{2}  q^{3} ) = 5pq+25 p^{3} q ^{4}
 x^{5} (7-16 x^{4}) = 7 x^{5} - 16 x^{9}
2mn (3m-4n+5mn) = 6 m^{2} n - 8m n^{2} + 10 m^{2}  n^{2}
 x^{2} (12x+7)=12 x^{3}+7 x^{2}
3 x^{3}(2 x^{2} - y^{2} )=6 x^{5}-3 x^{3}  y ^{2}

P.S. : Click "Thanks" if I helped. It'll be appreciated. :) 
0